1992
DOI: 10.1007/bf00591180
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy combined with endoscopic sphincterotomy and stone extraction or laparoscopic choledochoscopy and electrohydraulic lithotripsy for management of cholelithiasis with choledocholithiasis

Abstract: Six hundred twenty-two laparoscopic cholecystectomies were performed at St. Vincent Hospital over a 14-month period. We reviewed the records of 366 of these patients who were referred to the authors. Thirty-six patients had suspected choledocholithiasis. The primary author (M.E.A.) performed 38 endoscopic retrograde cholangiopancreatography (ERCPs) on these patients for diagnosis and management. Seventeen of the 36 patients had common bile duct stones; 19 patients had negative studies. Of the 17 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
3

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 30 publications
0
40
0
3
Order By: Relevance
“…Its advantages are associated with treatment in a single procedure, low morbidity and mortality rates among selected patients, short hospital stay, and rapid return to normal activities. As previously demonstrated, the transcystic approach is technically feasible in most cases, and is associated with a high rate of biliary clearance in selected patients [2,5,10,16,17]. Despite the preference of some authors [16,17] for the initial use of a choledochoscope, this procedure requires cystic dilation in some cases and has limitations in retrieving larger stones.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Its advantages are associated with treatment in a single procedure, low morbidity and mortality rates among selected patients, short hospital stay, and rapid return to normal activities. As previously demonstrated, the transcystic approach is technically feasible in most cases, and is associated with a high rate of biliary clearance in selected patients [2,5,10,16,17]. Despite the preference of some authors [16,17] for the initial use of a choledochoscope, this procedure requires cystic dilation in some cases and has limitations in retrieving larger stones.…”
Section: Discussionmentioning
confidence: 92%
“…Choledocholithiasis, however, has been managed by pre-, intra-, or postoperative ERCP. Some authors [1,2] have demonstrated the effectiveness of the pre-and postoperative endoscopic approach with high success rates, low morbidity and mortality, and a short hospital stay. However, some disadvantages have been observed, such as the need for more than one procedure, success rates of about 90%, unnecessary preoperative ERCP due to the low predictability rates of laboratory tests and ultrasonography, and the probability of failure in postoperative procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although perioperative endoscopic retrograde cholangiopancreatography (ERCP) may be a preferred method for handling CBD stones in the laparoscopic era [4], laparoscopic CBD exploration is also being promoted [1,5,6]. We have developed a simple pig model which has assisted us in practicing advanced laparoscopic biliary procedures in the animal laboratory.…”
Section: Abstract: Laparoscopic Biliary Surgery --Common Bile Duct Ementioning
confidence: 99%
“…We disagree with a few points in Dr. Arregui's recent article [1]. We believe that preoperative ERCP/ES should be restricted to elderly patients or patients with cholangitis.…”
mentioning
confidence: 83%